Medical knowledge of medieval physician on the cause of plague during 1347/8-1351: traditional understandings to poison theory - Sang Dong LEE (Uisahak, 2022)
This article sets its investigative goal on determining the medical knowledge of medieval physicians from 1347-8 to 1351 concerning the causes of plague. As the plague killed a third of Europe’s population, the contemporary witness at the time perceived God as the sender of this plague to punish the human society. However, physicians separated the religious and cultural explanation for the cause of this plague and instead seek the answer to this question elsewhere. Developing on traditional medical knowledges, physicians classified the possible range of the plague’s causes into two areas: universal cause and individual/particular causes. In addition, they also sought to explain the causes by employing the traditional miasma-humoral theory. Unlike the previous ones, however, the plague during 1347-8 to 1351 killed the patients indiscriminately and also incredibly viciously. This phenomenon could not be explained by merely using the traditional medical knowledge and this idiosyncrasy led the physicians employ the poison theory to explain the causes of plague more pragmatically.